Ghosts and religious life in early China - Pu, Muzhou 1952- (Cambridge New York Cambridge University Press, 2022)
Ghost : the other side of humanity -- The emergence of ghosts in early China -- Imperial order and local variations -- Stories that reveal the dark corner -- Ghosts in early Daoist religious culture -- The taming of ghosts in early Buddhism -- Chinese ghosts in a comparative perspective.
"For modern people, ghost stories are no more than thrilling entertainment. For those living in antiquity, ghosts were far more serious beings, as they could affect the life and death of people and cause endless fear and anxiety. How did ancient societies imagine what ghosts looked like, what they could do, and how people could deal with them? From the vantage point of modernity, what can we learn about an obscure, but no less important aspect of an ancient culture? In this volume, Mu-chou Poo explores the ghosts of ancient China, the ideas that they nurtured, and their role in its culture. His study provides fascinating insights into the interaction between the idea of ghosts and religious activities, literary imagination, and social life devoted to them. Comparing Chinese ghosts with those of ancient Egypt, Mesopotamia, Greece, and Rome, Poo also offers a wider perspective on the role of ghosts in human history. Mu-Chou Poo is Professor of History at the Chinese University of Hong Kong. He is the author of Wine and Wine Offering in the Religion of Ancient Egypt (2014), In search of Personal Welfare: A View of Ancient Chinese Religion, and Daily Life in Ancient China (1998)"--
Includes bibliographical references and index
Keywords: Ghosts -- China -- History; SOCIAL SCIENCE / Archaeology; China -- Religion -- History